Assessment of Perceived Health Care Access in a Rural Community in Rizal: A Cross-sectional Study - Kathyrine Calong Calong; Judalyn Comendador (San Beda University, 2019)
Background: Access to health care is considered a basic right and integral to human life. However, this still remains a challenge especially in developing countries where the majority of the poor reside and suffer from a disproportionate amount of disease. The study determined the six key components of health care access: approachability, availability, accessibility, affordability, acceptability, and accommodation, as perceived by a rural community in Taytay, Rizal, Philippines. Methods: This descriptive-cross sectional study included a convenience sample of 62 participants. The Perceived Access to Health Care Instrument was utilized. Frequency, percentage, mean, standard deviation, and univariate linear regression were used to analyze the data. Results: The study revealed that health care access was rated as good in terms of approachability, availability, affordability and acceptability. On the other hand, accessibility and accommodation was rated as fair. It was also revealed that none of the demographic profiles significantly predicted the perceived access to health care Conclusion: Assessment of health care access is an important measure of health care equity and despite several factors previously shown to affect health care access, the results of this study showed that the participants have good access to health care in their community